2005
DOI: 10.1002/ps.1008
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate‐resistant crops: history, status and future

Abstract: The commercial launch of glyphosate-resistant soybeans in 1996 signaled the beginning of a new era in weed management in row crops. Today, over 80% of the soybeans grown in the USA are glyphosate resistant. Since that time, many crops have been transformed that have allowed crop applications of many classes of herbicide chemistries. Crops currently under production include maize, soybean, cotton and canola. Transformation technology and selection methods have improved and the rate of development as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
194
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(199 citation statements)
references
References 14 publications
(17 reference statements)
1
194
0
4
Order By: Relevance
“…Although class I enzymes have been used to generate glyphosate-resistant crops, virtually all commercial crops with this trait, such as soybeans, corn, cotton, and canola, express the Agrobacterium tumefaciens strain CP4 class II protein (Dill, 2005). In this study, sequence analysis and structure modeling demonstrated that AroA Pantoea sp most closely resembles a class I EPSPS and possesses high glyphosate tolerance.…”
Section: Discussionmentioning
confidence: 92%
“…Although class I enzymes have been used to generate glyphosate-resistant crops, virtually all commercial crops with this trait, such as soybeans, corn, cotton, and canola, express the Agrobacterium tumefaciens strain CP4 class II protein (Dill, 2005). In this study, sequence analysis and structure modeling demonstrated that AroA Pantoea sp most closely resembles a class I EPSPS and possesses high glyphosate tolerance.…”
Section: Discussionmentioning
confidence: 92%
“…The students previously heard very little about the mechanisms of biotechnology (Gerald& Dill, 2005), and about important drugs manufactured by genetic engineering methods (Fusek, Kas & Ruml, 2008). They knew nothing about the many enzymes we consume every day in our baked products, yoghurts, cheese, soft drinks and spirits that have been produced by genetically engineered microorganisms and that must be included in the Community Register of GM food and feed.…”
Section: Biotechnologymentioning
confidence: 99%
“…The acceptance and wide spread use of RoundUp Ready technology, in which a crop species is transformed with a gene conferring RoundUp tolerance, has led to skyrocketing use of glyphosate, the active ingredient in the herbicide RoundUp (Dill, 2005). Unfortunately, morning glory species are also notoriously difficult to control with this herbicide, and are becoming more prominent in glyphosate resistant crops (Culpepper, 2006).…”
Section: Ipomoea and The Evolution Of Plant-parasite Interactionsmentioning
confidence: 99%